1945 [videorecording (DVD)] - Török, Ferenc, 1971-; Rudolf, Peter; Tasnádi, Bence, 1988-; Angelus, Iván; Szánto, T. Gábor, 1966- (Menemsha Films, 2018)
"On a summer day in 1945, an Orthodox man and his grown son return to a village in Hungary while the villagers prepare for the wedding of the town clerk's son. The townspeople-- suspicious, remorseful, fearful, and cunning-- expect the worst and behave accordingly. The town clerk fears the men may be heirs of the village's deported Jews and expects them to demand their illegally acquired property back"--Container.